The influence of modified Qing E Formula on the differential expression of serum exosomal miRNAs in postmenopausal osteoporosis patients - Lu, Junjie; Wu, Hui; Jin, Huan; He, Ziyi; Shen, Lin; Ma, Chen; Xu, Xiaojuan; Wang, Zixian; Shuai, Bo (Frontiers in Pharmacology, 2024)
Objective: Although guidelines support the efficacy of Modified Qing’ E Formula (MQEF) in treating postmenopausal osteoporosis (PMOP), its underlying mechanisms remain incompletely understood. This retrospective investigation aims to elucidate MQEF's impact on serum exosomal miRNA expression in postmenopausal osteoporosis patients and to explore potential therapeutic mechanisms. Methods: Following ethical approval and registration, postmenopausal osteoporosis patients aged 50-85 years, meeting the diagnostic criteria were randomly selected and received MQEF decoction supplementary therapy. Serum samples were collected pre- and post-treatment, followed by isolation and sequencing of exosomal miRNAs. Differential miRNAs in serum exosomes were identified, and bioinformatics analysis was conducted to discern the principal exosomal miRNAs involved in MQEF's effects on PMOP and the associated signaling pathways. Results: 18 clinical blood samples were collected. A total of 282,185 target genes were detected across the three groups. 306 miRNAs exhibited altered expression in serum exosomes of PMOP patients, while MQEF intervention resulted in changes in 328 miRNAs. GO enrichment analysis revealed the immune and endocrine systems was pertained. KEGG enrichment analysis indicated associations between PMOP occurrence and MQEF treatment with cytokine interactions, oxidative phosphorylation, and the renin-angiotensin system. Intersectional analysis identified 17 miRNAs, including 2 consistent trends. miR-3188 as a potentially pivotal miRNA implicated in both PMOP occurrence and MQEF treatment. Conclusion: This study constitutes the first randomized, retrospective clinical exploration confirming that MQEF demonstrates regulatory influence over exosomal miRNA expression in PMOP patients' serum, its impact likely involves modulation of the immune and endocrine systems, as well as the renin-angiotensin system.